Symptomatic intracerebral hemorrhage in proximal and distal medium middle cerebral artery occlusion patients treated with mechanical thrombectomy - Yedavalli, Vivek S.; Salim, Hamza Adel; Musmar, Basel; Adeeb, Nimer; Essibayi, Muhammed Amir; ElNaamani, Kareem; Henninger, Nils; Sundararajan, Sri Hari; Kuhn, Anna Luisa; Khalife, Jane; Ghozy, Sherief; Scarcia, Luca; et al. (Journal of neuroInterventional surgery)
Background - Acute ischemic stroke (AIS) caused by distal medium vessel occlusions (DMVOs) represents a significant proportion of overall stroke cases. While intravenous thrombolysis (IVT) has been a primary treatment, advancements in endovascular procedures have led to increased use of mechanical thrombectomy (MT) in DMVO stroke patients. However, symptomatic intracerebral hemorrhage (sICH) remains a critical complication of AIS, particularly after undergoing intervention. This study aims to identify factors associated with sICH in DMVO stroke patients undergoing MT. - - - Methods - This retrospective analysis utilized data from the Multicenter Analysis of Distal Medium Vessel Occlusions: Effect of Mechanical Thrombectomy (MAD-MT) registry, involving 37 centers across North America, Asia, and Europe. Middle cerebral artery (MCA) DMVO stroke patients were included. The primary outcome measured was sICH, as defined per the Heidelberg Bleeding Classification. Univariable and multivariable logistic regression were used to identify factors independently associated with sICH. - - - Results - Among 1708 DMVO stroke patients, 148 (8.7%) developed sICH. Factors associated with sICH in DMVO patients treated with MT included older age (adjusted odds ratio (aOR) 1.01, 95% confidence interval (95% CI) 1.00 to 1.03, P=0.048), distal occlusion site (M3, M4) compared with medium occlusions (M2) (aOR 1.71, 95% CI 1.07 to 2.74, P=0.026), prior use of antiplatelet drugs (aOR 2.06, 95% CI 1.41 to 2.99, P<0.001), lower Alberta Stroke Program Early CT Scores (ASPECTS) (aOR 0.75, 95% CI 0.66 to 0.84, P<0.001), higher preoperative blood glucose level (aOR 1.00, 95% CI 1.00 to 1.01, P=0.012), number of passes (aOR 1.27, 95% CI 1.15 to 1.39, P<0.001), and successful recanalization (Thrombolysis In Cerebral Infarction (TICI) 2b-3) (aOR 0.43, 95% CI 0.28 to 0.66, P<0.001). - - - Conclusion - This study provides novel insight into factors associated with sICH in patients undergoing MT for DMVO, emphasizing the importance of age, distal occlusion site, prior use of antiplatelet drugs, lower ASPECTS, higher preoperative blood glucose level, and procedural factors such as the number of passes and successful recanalization. Pending confirmation, consideration of these factors may improve personalized treatment strategies.